2011
DOI: 10.1007/s00404-011-2040-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune thyroiditis in patients with polycystic ovary syndrome

Abstract: In this case-control study, anti-thyroid antibodies and goiter prevalence were significantly higher in PCOS patients. These data suggest that thyroid exam and evaluation of thyroid function and autoimmunity should be considered in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 13 publications
1
57
0
8
Order By: Relevance
“…17,33 Similarly, in patients with polycystic ovarian disease ATA positivity was significantly higher compared to control group. 42,43 Even association of this antibody positivity with premature ovarian insufficiency was also suggested. 17 According to the hypothesis of a recent study, zona pellucida becomes a target for ATA since it has antigen groups similar to thyroid and thus fertility was negatively affected.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 88%
“…17,33 Similarly, in patients with polycystic ovarian disease ATA positivity was significantly higher compared to control group. 42,43 Even association of this antibody positivity with premature ovarian insufficiency was also suggested. 17 According to the hypothesis of a recent study, zona pellucida becomes a target for ATA since it has antigen groups similar to thyroid and thus fertility was negatively affected.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 88%
“…Therefore, we searched for recent reports on screening studies of TgAb and TPOAb. To avoid the influence of diseases themselves, we only considered studies done on healthy control subjects in various regions in different countries [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In healthy subjects, the incidence of positive TgAb or TPOAb is …”
Section: Discussionmentioning
confidence: 99%
“…PCOS patients had higher mean TSH levels, a higher prevalence of goiter (27.5 vs 7.5%), and more frequently a hypoechoic thyroid ultrasound pattern (12.5 vs 2.5%) than controls (22). Recently, a case-control Iranian study has demonstrated that, in PCOS patients, the mean level of TPO antibodies and the prevalence of clinically proven goiter were higher than those in controls without PCOS (23). However, concentrations of TSH and Tg antibodies did not differ between PCOS and controls (23).…”
Section: Joint Prevalencementioning
confidence: 98%
“…Recently, a case-control Iranian study has demonstrated that, in PCOS patients, the mean level of TPO antibodies and the prevalence of clinically proven goiter were higher than those in controls without PCOS (23). However, concentrations of TSH and Tg antibodies did not differ between PCOS and controls (23). Only one Turkish study was not able to establish higher levels of TPO and Tg antibodies in 84 women with PCOS than in 81 controls, although thyroid diseases were more prevalent in patients (24).…”
Section: Joint Prevalencementioning
confidence: 99%